Transcriptome analysis of methicillin-resistant Staphylococcus aureus in response to stigmasterol and lupeol - Adnan S.-N.-A.; Ibrahim N.; Yaacob W.A. (Elsevier Ltd, 2024)
Objectives Methicillin-resistant Staphylococcus aureus (MRSA) is an important pathogen with multiple antibiotic resistance that causes morbidity and mortality worldwide. Multidrug-resistant (MDR) MRSA with increased resistance to currently available antibiotics has challenged the world to develop new therapeutic agents. Stigmasterol and lupeol, from the plant Phyllanthus columnaris, exhibit antibacterial activities against MRSA. The aim of this study was to utilise next-generation sequencing (NGS) to provide further insight into the novel transcriptional response of MRSA exposed to stigmasterol and lupeol. Methods Timekill analysis of one MRSA reference strain (ATCC 43300) and three clinical isolates (WM3, BM1 and KJ7) for both compounds was first performed to provide the bacteriostatic/bactericidal profile. Then, MRSA ATCC 43300 strain treated with both compounds was interrogated by NGS. Results Both stigmasterol and lupeol possessed bacteriostatic properties against all MRSA tested; however, lupeol exhibited both bacteriostatic and bactericidal properties within the same minimum inhibitory concentration and minimum bactericidal concentration values against BM1 (12.5 mg/mL). Transcriptome profiling of MRSA ATCC 43300 revealed significant modulation of gene expression with multiple desirable targets by both compounds, which caused a reduction in the translation processes leading to inhibition of protein synthesis and prevention of bacterial growth. Conclusions This study highlights the potential of both stigmasterol and lupeol as new promising anti-MRSA agents. 2016 International Society for Chemotherapy of Infection and Cancer